Determining Factors of Consumer Purchases Decisions in MSME BUMDesa Kuala Alam Bandar Jaya - Arimurti, Rizqa; Raflah, Wan Junita; Rambe, Armita Novriana (Journal Economy and Currency Study (JECS), 2023)
This research aims to determine the factors that influence purchases decisions at UMKM BUMDesa Kuala Alam Bandar Jaya, focusing on product innovation, product quality, and brand awareness. The population in this study were people in the Bengkalis City area. The sampling technique uses the accidental sampling method with the expected research sample being around 80 to 100 respondents. From the survey results, the research sample obtained was 85 respondents. The data source used is primary data, namely the researcher distributed questionnaires to the community in Bengkalis City. The data analysis method for this research uses Multiple Linear Regression analysis. The measurement indicators for this research use a Likert Scale and the data is processed using SPSS version 25. Based on the research results, it shows that the factors that influence purchases decisions in UMKM BUMDesa Kuala Alam Bandar Jaya are product innovation, product quality, and brand awareness. It is hoped that this research can contribute to the MSME BUMDES Kuala Alam Bandar Jaya by revealing the importance of recognizing the role of product innovation, product quality, and brand awareness in managing MSME business operations. This is a form of helping MSMEs to maintain the continuity and growth of their business, while achieving optimal income.